2022
DOI: 10.4081/jphia.2022.2415
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of organizational culture factors that influence the performance of health care professionals: A literature review

Abstract: Hospitals in today’s healthcare system are under pressure to boost their competitiveness. A number of studies have shown the disconnect between corporate culture and the enhancement of healthcare professionals’ performance. While it is well accepted that an organization’s culture has a substantial impact on the performance of its health care professionals in clinical practice, the mechanisms by which culture might enhance health care professionals’ performance remain unclear. This paper draws on 22 literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…These findings were documented in a cross-sectional study conducted in Saudi Arabia, revealing a significant association between barriers to engaging in genetic research and participants who were younger and less educated. 16 In contrast, numerous other studies did not find a correlation between education and the consent to participate in genetic research. [17][18][19][20] This incongruity may be attributed to the diversity of diseases under investigation, variations in geographical locations and populations, coupled with the inherent disparities in educational strata ranging from graduate degrees to collegiate education.…”
Section: Discussionmentioning
confidence: 92%
“…These findings were documented in a cross-sectional study conducted in Saudi Arabia, revealing a significant association between barriers to engaging in genetic research and participants who were younger and less educated. 16 In contrast, numerous other studies did not find a correlation between education and the consent to participate in genetic research. [17][18][19][20] This incongruity may be attributed to the diversity of diseases under investigation, variations in geographical locations and populations, coupled with the inherent disparities in educational strata ranging from graduate degrees to collegiate education.…”
Section: Discussionmentioning
confidence: 92%
“…The development and revision of nursing curricula are influenced by the contributions of various stakeholders, including nurse supervisors, students, clinicians, and educators (Axtell et al, 2010). Their participation guarantees that the curriculum maintains its pertinence, contemporaneity, and congruence with the requirements of the nursing vocation (Almutairi et al, 2022). Stakeholder identification is a critical component of nursing curriculum development involving stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…An all-encompassing strategy incorporating ongoing communication, attentive listening, and collaboration is also essential for the successful management of stakeholder engagement (Aditya et al, 2021). The stakeholder engagement methodology ought to be formulated with the vision for stakeholder participation in mind, with explicit delineation of objectives, participants, approaches, and obligations (Almutairi et al, 2022). The responsibility of nursing education is to undergo a transformation in order to correspond with the demands of present and future practice (Aditya et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing professionals working in the field of mental health are especially at risk for experiencing burnout and caregiver weariness [6] , investigated the causes of this national issue. In response to "widespread concern about the mental health caregiver workforce in Australia," the Australian Health Minister's Advisory Council asked them to conduct a scoping assessment of the Mental Health Caregiving System Down Under.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that those working inward were more likely to feel disconnected from their patients, less likely to feel empathy for them, and more likely to be dissatisfied and pessimistic about their careers. Caregivers in the field of psychiatry often spend a lot of time with, and emotionally invest in, their patients who suffer from serious mental illness, which has been linked to increased stress levels for those [6] . Acknowledging a number of challenges associated with mental health caregivers and the nature of providing care for seriously disturbed patients in an unpredictable context, some staff members have criticized efforts to preserve professional care standards for mental health caregivers [7] .…”
Section: Introductionmentioning
confidence: 99%